How supply shocks drive disagreement in monetary policy - Madeira, C.; Madeira, J.; Santos Monteiro, P. (SUERF Policy Brief, 2023)
We investigate how dissent in the Federal Open Market Committee (FOMC) is affected by structural macroeconomic shocks. We find that dissent is less frequent when demand shocks are the predominant source of fluctuations, and more frequent for supply shocks. In addition, supply shocks are found to raise private sector forecasting uncertainty about the path of interest rates. Since supply shocks impose a trade-off between inflation and output stabilization while demand shocks do not, our findings are consistent with heterogeneous preferences among FOMC members around the Fed’s dual mandate for price stability and employment.